Deposition of Visible Light Active Photocatalytic Bismuth Molybdate Thin Films by Reactive Magnetron Sputtering - Ratova, Marina (Materials (Basel), 2016)
Bismuth molybdate thin films were deposited by reactive magnetron co-sputtering from two metallic targets in an argon/oxygen atmosphere, reportedly for the first time. Energy dispersive X-ray spectroscopy (EDX) analysis showed that the ratio of bismuth to molybdenum in the coatings can be effectively controlled by varying the power applied to each target. Deposited coatings were annealed in air at 673 K for 30 min. The crystalline structure was assessed by means of Raman spectroscopy and X-ray diffraction (XRD). Oxidation state information was obtained by X-ray photoelectron spectroscopy (XPS). Photodegradation of organic dyes methylene blue and rhodamine B was used for evaluation of the photocatalytic properties of the coatings under a visible light source. The photocatalytic properties of the deposited coatings were then compared to a sample of commercial titanium dioxide-based photocatalytic product. The repeatability of the dye degradation reactions and photocatalytic coating reusability are discussed. It was found that coatings with a Bi:Mo ratio of approximately 2:1 exhibited the highest photocatalytic activity of the coatings studied; its efficacy in dye photodegradation significantly outperformed a sample of commercial photocatalytic coating.